Visual cryptographic techniques for secret image sharing: a review. Issue 5 (2nd November 2018) - Sharma, Ram Gopal; Dimri, Priti; Garg, Hitendra
ABSTRACT: A visual cryptography scheme (VCS) allows one to decrypt images without any knowledge of cryptography and computational efforts. VCS allows secret image sharing such that we can divide the original image into meaningful or nonmeaningful shares. The shares are distributed among participants; during decryption, the original secret image is recovered through stacking all or some of the shares by the human visual system. Various techniques of visual cryptography were constructed mainly for binary images but later, they were enhanced to handle gray-scale or color images. This article focuses on the study of various visual cryptographic schemes and analyses the performance on the basis of various parameters such as, pixel expansion, type of shares generated, image format, number of secret images, encryption method, etc.. In the proposed work, we give a precise and complete review of various visual cryptographic schemes based on different research works related to this area and cite the relevant literature.